Disparidades regionais na mortalidade por doença isquêmica do coração no estado do Paraná e uma avaliação a partir do nível local (municipal) sobre o acesso ao tratamento do infarto agudo do miocárdio com supradesnivelamento do seguimento ST - Andrade, Luciano de (2014)
High technology in the field of interventional cardiology applied in tertiary hospitals has brought enormous benefits in the treatment of ischemic heart disease (IHD). However, for Acute Myocardial Infarction with Elevation of the ST Segment (STEMI) mortality rates from IHD remain high, affecting especially developed countries and becoming increasingly problematic in developing countries. In the present study were evaluated the relationship between the rate of IHD mortality and the socioeconomic, demographic and geographic conditions in 399 cities in the state of Paraná, Brazil from 2006 to 2010. Furthermore, the factors related to delays in treatment of patients with STEMI in a tertiary hospital (Reference Interventional Cardiology Center) were taken into account to support a strategic plan for structural and staff changes in a primary hospital, aligning the process with international guidelines. Data on IHD mortality in the state of Parana were obtained from the Mortality Information System (SIM) of the Ministry of Health. The population, socioeconomic and demographic information were provided in digital format by the Brazilian Institute of Geography and Statistics (IBGE). Additional data to assess the delays in the treatment of STEMI patients in a tertiary hospital transported from a primary hospital were obtained from medical records and interviews. We used different methods: Exploratory Spatial Data Analysis (ESDA); and a qualitative and quantitative integrated analysis, including on-site observations, interviews, examination of medical records, Qualitative Comparative Analysis (QCA) and Dynamic Systems Modeling (SD). For the treatment of data, were used the softwares GeoDATM, NVivo version 10.0, statistical R version 2.15.0 and Vensim DSS ® version 5.11. In Exploratory Spatial Data Analysis (ESDA) was found a positive spatial autocorrelation regarding IHD mortality (I = 0.5913, p = 0.001) in Parana state. There was a significant positive spatial association between each of the three socioeconomic and demographic indicators and the rate of IHD mortality: Elderly Population Index (I = 0.3436 p = 0.001), Illiteracy Rate (I = 0.1873 p = 0.001) and Municipal Human Development Index (HDI-M) (I = 0.0900 p = 0.001). In addition, two other indicators showed significant negative association with IHD mortality rate: Adjusted population (I = -0.1216 p = 0.001) and Gross Domestic Product (I = -0.0864 p = 0.001). A positive spatial association was also found between mortality rates from IHD and the geographic distances between city of residence of the patients and their corresponding reference interventional cardiology center (I = 0.3368 p = 0.001). Cities located within Regional Health with reference interventional cardiology center had a significantly lower rate of IHD mortality. The high rate of IHD mortality within the Regional Health Services was not restricted to socioeconomic and demographic variables and presented positive correlation with the distance between each city and its reference interventional cardiology center. When the factors associated with delays in treatment of patients with STEMI were analyzed from primary hospital, the main causes were categorized into three themes: a) professional b) equipment c) transportation logistics. Qualitative comparative analysis (QCA) confirmed four main stages of delays for the care of patients with STEMI versus ?Door-In to Door-Out? time at the primary hospital. These stages and their average delays in minutes, were: a) First medical contact (from the gateway to the first contact with the nurse and / or physician): 7 minutes; b) Acquisition of electrocardiogram (ECG) and evaluation by a physician: 28 minutes; c) Transmission of ECG and tertiary hospital feedback (reference interventional cardiology center) time: 76 minutes; d) Waiting times for patient transfer: 78 minutes. The baseline Model of System Dynamics confirmed the system's behavior overall delays that occurred and the need for improvements. Moreover, after the validation of the sensitivity analysis, the results suggested that an overall improvement of 40% to 50% in each of these identified phases would reduce the delay. We conclude that geographic factors play a significant role in IHD mortality within the municipalities of the state of Parana and have important policy implications with regard to heart health care networks? geographic distribution. In loco, evaluation of the delay in STEMI patients? treatment suggests that investment in training of health personnel, the reduction of bureaucracy and management guidelines can lead to important improvements decreasing the detected delay.